Isolation and Characterization of Cetacean Cell-Derived Extracellular Vesicles - Valentina Moccia; Cinzia Centelleghe; Ilaria Giusti; Antonella Peruffo; Vincenza Dolo; Sandro Mazzariol; Valentina Zappulli (Animals, 2023)
Cetaceans are of scientific interest because they are good candidates as environmental bioindicators. However, in vivo research is arduous and in vitro studies represent a rarely used valid alternative. Extracellular vesicles (EVs) are membrane-bound structures playing roles in cell-to-cell communication. Despite being a promising investigative tool in different fields of science, EVs have been poorly studied in cetaceans. To fill this gap, we describe the preliminary characterization of EVs isolated from a bottlenose dolphin and a Cuvier’s beaked whale cell line. EVs have been isolated with ultracentrifugation (UC) or size exclusion chromatography (SEC) and characterized with nanoparticle tracking analysis (NTA), Western blotting (WB), and scanning transmission electron microscopy (STEM). UC and SEC allowed the isolation of mainly small EVs (<200 nm). A higher number of particles were isolated through UC compared to SEC from both cell lines. At WB, all EVs expressed the EV-markers CD9 and integrin-β. Only EVs isolated with UC were positive for TSG101. In conclusion, we isolated for the first time EVs from a bottlenose dolphin and a Cuvier’s beaked whale cell line using two different techniques. Further studies on cell-derived EVs will be useful to deepen our knowledge on cetacean pathophysiology and health status assessment.